Constructivism in ethics - Bagnoli, Carla, 1966- (New York : Cambridge University Press, 2013)
Are there such things as moral truths? How do we know what we should do? And does it matter? Constructivism states that moral truths are neither invented nor discovered, but rather are constructed by rational agents in order to solve practical problems. While constructivism has become the focus of many philosophical debates in normative ethics, meta-ethics, and action theory, its importance is still to be fully appreciated. These new essays written by leading scholars define and assess this new approach in ethics, addressing such questions as the nature of constructivism, how constructivism improves our understanding of moral obligations, how it accounts for the development of normative practices, whether moral truths change over time, and many other topics. The volume will be valuable for advanced students and scholars of ethics and all who are interested in questions about the foundation of morality.'--Book Jacket.
Introduction / Carla Bagnoli -- Moral skepticism, constructivism, and the value of humanity / Robert Stern -- How not to be an ethical constructivist : a critique of Korsgaard's neo-Kantian constitutivism / William J. FitzPatrick -- Kant's constructivism / Oliver Sensen -- Meta-ethics and its discontents : a case study of Korsgaard / Nadeem J. Z. Hussain and Nishi Shah -- Is constructivism an alternative to moral realism? / David Copp -- Constructivism and practical knowledge / Stephen Engstrom -- Constructivism about practical knowledge / Carla Bagnolia -- Constructivism and particularism / Mark LeBar -- Constructive complaints / Thomas Baldwin -- Revising moral norms : pragmatism and the problem of perspicuous description / Henry S. Richardson.
Includes bibliographical references (pages 243-253) and index.
Keywords: Constructivism (Philosophy).; Ethics